Analisis Makna Denotatif dan Konotatif pada Istilah di Game Online Mobile Legends: Bang Bang - Mohamad Yusri Romadhon; Ubaedillah Ubaedillah; Robert Rizki Yono (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the denotative and connotative meaning of the online game Mobile Legend: Bang. The method used in this study is a qualitative descriptive method. The source of data in this study is the grand finale of MPL ID Season 9. The data in this study are words in the use of terms in the online game Mobile Legend: Bang Bang which contain denotative and connotative meanings. Data collection techniques used are recording, listening, and note-taking techniques. The data analysis technique in this study used descriptive analysis. Data analysis used is data reduction, data presentation, and drawing conclusions or verification. The results show that the meanings of many terms have connotative meanings, meaning that there are other meanings from the actual meanings and these meanings depend on the context. The context used in this term is when playing the online game Mobile Legend